Redesign of Dust Filter Tools in Small and Medium Industries (IKM) by Integrating Reverse Engineering and Root Cause Analysis (RCA) - Ika Sasmita Sari; Wiwik Sulistiyowati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
Gerandong crackers are different types of crackers with other crackers, the main ingredients gerandong crackers derived from the ready-made crackers, gerandong crackers production process consists of several stages one of which is the dust filter stage. At this stage use the filter tool. In terms of use, this tool is working properly. However, this tool is still not effective, it needs to be redesigned on the tool to improve. The results of this study include: Improving the design of dust filters in the process of making gerandong crackers in terms of how to use reverse engineering methods. From design that can be expected can be repaired from dust filter tool. Recommendations to reduce air pollution are less effective. The Efforts to improve the design of dust filter equipment in this study using reverse engineering methods assisted by CAD (Computer Aided Design), in this case solidwork software and will be integrated with Root Cause Analisys. The result of this research is a new design of dust filter tool that is practical and effective, practically not doing a lot of arrangement and switching tool when will production, effective in reducing dust when production and output yielded cleaner than before